Model Penyelesaian Konflik Alat Tangkap Perikanan di Aceh Barat - Sulaiman Sulaiman (Universitas Syiah Kuala, 2013)
ABSTRACT: The conflict of trawl has been occurring for long time in Aceh. Using trawl is not only illegal but also resulted in a decrease of catcher number got by fishermen in the place. This article aims to explain the conflict in Lhok Meureubo in relation to the legal ban of the usage of trawl, the conflict settlement process, as well as the steps taken by the Government of West Aceh district in anticipating its usage in the future. The methods applied include normative and empirical research. The normative research is done through legal materials. While the empirical one is conducted by interviewing a sample of purposively selected sample. The conflict in Lhok Meureubo is due to the use of trawling gear, it has been happening since 2003. The conflicts come up by the use of trawl types that are not environmentally friendly. The use of such fishery catcher has been taking time for a long time, but after the tsunami, the use of mini-trawling increasingly from a variety of aid for tsunami victims. The steps taken by the Government of West Aceh district to overcome the problem in the future, is especially by replacing the trawl gear with the one that is more environmentally friendly. The fishermen who use the trawl which the boat already registered is then reported to the Department of Marine and Fisheries of West Aceh district to get the trawl replaced by environmentally friendly trawl. A Settlement Model of Trawl Conflict in West Aceh